ASPECTOS ECOLOGICOS DE UNA POBLACION DE ROEDORES EN LA CORDILLERA ORIENTAL COLOMBIANA - Pérez Torres, Jairo; Coordinador Programa Chocó Biogeográfico, Unidad de Ecología y Sistemática (UNESIS), Departamento de Biología, Facultad de Ciencias, Pontificia Universidad Javeriana, Bogotá (2013)
Distribution, abundancy, demographic structure, type of spatial pattems and home range of a population ofThomasomys laniger (Thomas, 1895) (RODENTIA: CRICETIDAE) from Valledel Frailejón (Frailejon valley) in Chingaza Natural National Park, on the Oriental mountain chain (cordillera Oriental) in Department of Cundinamarca, were studied from January to December of 1992.· The variation ofthe population pattems according to seasonality based on frecuency of capture ofmice in diferent trapping phases was established. An approximation to its demographic dynamics was obtained through population and development curves.